Revision of the genus Exsuperantia Özdikmen, 2009 (Tetractinellida: Phymaraphiniidae) with description of a new species from the Atlantic Ocean - Carvalho, Francisca C.; Pisera, Andrzej (Zootaxa, 2019)
Phymaraphiniidae Schrammen 1924 (Porifera: Astrophorina) is a family of lithistid demosponges that has received little attention in the past decades. The systematic problems within this family have not been addressed for a long time due to the absence of new records and material. The genus Exsuperantia Özdikmen 2009 was first described by Schmidt (1879) as Rimella to allocate the species Rimella clava, found in the Caribbean. In 1892, Topsent found what he thought to be the same species described by Schmidt in the Azores, and synonymized it with Racodiscula clava, as he thought this species belonged to the family Theonellidae Lendenfeld 1903. However, Rimella and Racodiscula belong to distinct families: Rimella to Phymaraphiniidae, and Racodiscula to Theonellidae. Due to the fact that the genus Rimella was already preoccupied by a gastropod, it was renamed as Exsuperantia. In result of the poor preservation of Schmidt’s material and the absence of new specimens, the attribution of Topsent’s specimens to the family level remained obscure. Here, we review the genus Exsuperantia based on the analysis of new material recently collected during various research expeditions in the northeast Atlantic Ocean. The comparison of these new specimens with Schmidt’s and Topsent’s type material, allowed us to assign Topsent’s specimens to a new species, Exsuperantia archipelagus sp. nov., and confirm its attribution to the family Phymaraphiniidae (not Theonellidae). Phylogenetic reconstructions using newly generated sequences of the cytochrome subunit (COI) marker also support the assignment of the new species to the family Phymaraphiniidae (not Theonellidae).